Platelet Agglutinating Protein p37 Causes Platelet Agglutination through its Binding to Membrane Glycoprotein IV - Lian, Eric C-Y; Siddiqui, Farooq A; Jamieson, G A; Tandon, Narendra N (Thrombosis and Haemostasis, 1991)
A 37 kDa platelet agglutinating protein (PAP p37) has previously been shown to be present in a subset of patients with thrombotic thrombocytopenic purpura and has been purified from their plasma. Using solubilized platelet membrane proteins from normal donors, it was shown by Western blotting that r2sI-p37 bound to a membrane protein of 97 kDa (red/unred). Furthernore, the same protein was identified by reverse immunoblotting in which purified p37 was electrophoresed, transferred to the nitrocellulose sheet and incubated with solubilized normal platelet membrane proteins. The complex formed between p37 and the membrane protein was identified by autoradiography using polyclonal and monoclonal (OKM5) anti- GPIV antibodies, but was not detected by polyclonal antibody to GPIIIa. Similar studies with purified platelet GPIV under both reducing and non-reducing conditions demonstrated the binding of 125I-p37. Polyclonal and monoclonal antibodies to GPIV completely inhibited the platelet agglutination induced by TTP plasma containing p37, however, normal rabbit IgG, rabbit anti- GPIIIa IgG, and murine monoclonal anti-GPIIb/IIIa (10E5) antibodies had no effect. These data indicate that platelet GPIV is the receptor site for PAP p37.